Von Mises stress analyses using finite element model in two patients with chronic low back pain - Arief Indra Perdana Prasetya; Tri Indah Winarni; Jamari Jamari; Ardiyansyah Syahrom (Medicinski glasnik, 2026)
Aim: To investigate biomechanical properties of low back pain, which is a pervasive issue with a profound impact on an individual's quality of life due to pain and daily activity limitations. Methods: Two female patients suffering from chronic low back pain were presented. Patient 1 had severe compression fractures at L2 and L4, while Patient 2 had degenerative lumbar scoliosis due to L4-5 disc degeneration. We utilized Finite Element Analysis based on patient-specific CT scan data of lumbosacral 3D reconstruction to quantify the stress intensity as a measurement, known as Von Mises Stress. The reconstruction of the data was performed using specialized software, and simulations were conducted using Ansys 2020. To validate our results, we compared them to previous simulations. Results: Patient 1 exhibited the highest Von Mises stress in the annulus fibrosus at L2-L3 during axial rotation (84.168 MPa) and in the nucleus pulposus at L2-3 during anterior flexion (16.722 MPa). Patient 2 displayed the highest Von Mises stress both the annulus fibrosus and nucleus pulposus at L1-L2 during axial rotation (0.515 MPa and 0.0594 MPa, respectively). Conclusion: Our findings can help identify the segments at the highest risk for developing lumbar spondylosis and disc degenerative disorders by quantifying Von Mises stress in the lumbosacral region.
Keywords: disc degeneration; finite element analysis; low back pain; lumbarsacral spondylosis